Microfluidic systems for cancer diagnosis - Garcia-Cordero, Jose L. (Jose Luis); Revzin, Alexander (New York, NY : Humana Press, 2023)
This detailed volume explores recent developments in microfluidics technologies for cancer diagnosis and monitoring. The book is divided into two sections that delve into techniques for liquid biopsy for cancer diagnosis and platforms for precision oncology or personalized medicine in order to create effective patient avatars for testing anti-cancer drugs. Written for the highly successful Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step and readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Microfluidic Systems for Cancer Diagnosis serves as an ideal guide that will be helpful to either replicate the construction of microfluidic devices specifically developed for cancer diagnosis or to catalyze development of new and better cancer diagnostic devices.
Lateral Filter Array Microfluidic Devices for Detecting Circulating Tumor Cells -- Circulating Tumor Cell Cluster Sorting by Size and Asymmetry -- Digital Microfluidics with an On-Chip Drug Dispenser for Single or Combinational Drug Screening -- Affinity-Based Microfluidics Combined with Atomic Force Microscopy for Isolation and Nanomechanical Characterization of Circulating Tumor Cells -- Capture and Selective Release of Viable Circulating Tumor Cells -- Single-Response Electronic Tongue and Machine Learning Enable the Multidetermination of Extracellular Vesicle Biomarkers for Cancer Diagnostics without Recognition Elements -- Functional Interrogation of Ca2+ Signals in Human Cancer Cells In Vitro and Ex Vivo by Fluorescent Microscopy and Molecular Tools -- Microfluidic Protocols for the Assessment of Anti-Cancer Therapies in 3D Tumor-Stromal Co-Cultures -- A Microfluidic Approach for Enrichment and Single-Cell Characterization of Circulating Tumor Cells from Peripheral Blood -- Rapid On-Site Evaluation (ROSE): A Microfluidic Approach -- Microfluidic Acoustic Method for High Yield Extraction of Cell-Free DNA in Low-Volume Plasma Samples -- Isolation of Extracellular Vesicles by a Microfluidic Platform to Diagnose and Monitor Pancreatic Cancer -- High-Throughput Separation and Enrichment of Rare Malignant Tumor Cells from Large-Volume Effusions by Inertial Microfluidics -- SAIF: Label-Free Separation of Circulating Tumor Cells Using a Self-Amplified Inertial Focusing Microfluidic Chip -- Patient-Specific Microfluidic Cancer Spheroid Cultures for Testing Cancer Therapies -- Isolation of Cancer Cells from Liquid Biopsies Using 3D-Printed Affinity Devices -- A Microfluidic SERS Assay to Characterize the Phenotypic Heterogeneity in Cancer-Derived Small Extracellular Vesicles -- Cluster-Wells: A Technology for Routine and Rapid Isolation of Extremely Rare Circulating Tumor Cells Clusters from Unprocessed Whole Blood -- Secretion Function Analysis of Ex Vivo Immune Cells in an Integrated Microfluidic Device -- Dynamic Tumor Perfusion and Real-Time Monitoring in a Multiplexed 3D Printed Microdevice -- Capture and Release of Cancer Cells through Smart Bioelectronics -- Fabrication of Multilayer Microfluidic Arrays for Passive, Efficient DNA Trapping and Profiling.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (SpringerLink, viewed June 14, 2023).
Keywords: Cancer -- Molecular diagnosis; Biopsy; Microfluidic devices; Microfluidics; Neoplasms -- diagnosis; Neoplasms -- pathology; Liquid Biopsy -- methods; Microfluidic Analytical Techniques; Microfluidics; Biopsy; Cancer -- Diagnostic moléculaire.; Biopsie; Dispositifs microfluidiques; Microfluidique; Biopsy; Cancer -- Molecular diagnosis; Microfluidic devices; Laboratory Manual; Laboratory manuals; Manuels de laboratoire